Reaction of introduced bean (phaeolus) accessions to the infestation by thielaviopsis basicola (berkeleuy & broome) under natural epiphytotic conditons - Georgieva O.; Sofkova-Bobcheva SK (Federal State Budget Scientific Institution, 2015)
A periodic phytopathology field monitoring was conducted on 35 introduced common bean (Phaseolus) accessions at Maritsa Vegetable Crops Research Institute in 2014. The epiphytotic disease black root rot on the bean crops (over 75 % reduction of the stand) was recorded for the first time for the area of Bulgaria. The causal agent isolated from the plant tissue was identified as the fungus Thielaviopsis basicola (Berkeley) Ferraris. A strong relationship between disease severity variation and environmental and soil conditions was established. Black root rot was most severe when cool and wet weather occurred from seedling time to about three weeks after planting, combined with increased soil compaction. Field resistance was recorded in Bulgarian var. “Plovdivski zult”, var. “Starozagorski tzer” and line № 564 (3,66%, 5.33% and 6,50 % dumping-off of bean seedlings, respectively). Bean accession introduced from dry climate areas were highly susceptible to black root rot pathogen (over 76.0 % dumping-off of bean seedlings). Indirect relationship was found between bean tolerance to Th. basicola and presence of the anthocyanin in the hypocotyl and seed coat color. Install the average negative correlation between seed color signs (and hypocotyl) and the resistance of plants to Th. basicola. Samples with resistance to black root rot belong to the group with beige, red, brown or black color of seeds. The presence of phenolic compounds (anthocyanins) in the seed coat and hypocotyls beans can serve as an indirect indication of the selection of resistant to black rot breeding materials.
Keywords: common bean; black root rot; parasitism; durable field resistance